Division of Labour, Fertility Intentions, and Childbearing in Estonia - Gortfelder, Mark; Puur, Allan; Klesment, Martin (Comparative population studies, 2025)
Gender Revolution Theory offers a compelling hypothesis about the role of gender equality in contemporary fertility dynamics, suggesting that a more egalitarian division of paid and unpaid labour among couples will enhance childbearing. However, the empirical evidence supporting is weak. This study focuses on the division of labour and asks if couples in which the woman works full-time while also doing most of the housework have lower fertility intentions and parity progression. The study is set in Estonia, which experienced an early transition to full-time female employment, but also a prolonged period with a lack of egalitarianism in household work during the state socialist regime and afterwards. We use two family and fertility surveys conducted in the mid-1990s and the mid-2000s, both with a register follow-up. Applying ordinal and logistic regression models, we analyse both fertility intentions at the time of and actual childbearing in the five years following the surveys. We find that neither the fertility intentions nor the fertility behaviour of full-time employed women is higher in couples with a more equal division of housework, compared with couples in which the woman does most of the housework This finding applies regardless of parity. The conclusions are robust to a number of sensitivity analyses. The results call into question the relevance of division of labour as a factor in explaining socialist and post-socialist fertility behaviour.